Anti‐diabetic effect of andrographolide from Sambiloto herbs (Andrographis paniculata (Burm.f.) Nees) through the expression of PPARγ and GLUT‐4 in adipocytes - Novia Tri Astuti; Putri Rachma Novitasari; Raymond Tjandrawinata; Agung Endro Nugroho; Suwijiyo Pramono (Universitas Gadjah Mada, 2022)
Andrographolide has been shown to have a pharmacological effect as an antidiabetic. Nevertheless, the comprehensive mechanism of action has yet to be determined. Andrographolide is a primary component of the sambiloto herb (Andrographis paniculata (Burm.f.) Nees), in which a simple isolation process can obtain high yields. This study aimed to explain the anti‐diabetic effect of andrographolide compared to pioglitazone (a positive control) on glucose uptake by measuring the expression levels of peroxisome proliferator‐activated receptor gamma (PPARγ) and glucose transporter type 4 (GLUT‐4) genes in 3T3‐LI mouse adipocytes as an in vitro model. The differentiation of mature adipocytes from 3T3‐L1 fibroblasts was induced with 3‐isobutyl‐1‐methylxanthine, dexamethasone, and insulin. Andrographolide was provided through direct isolation from A. paniculata herbs. The gene expression was detected using the reverse transcription‐polymerase chain reaction (RT‐PCR). Pioglitazone and andrographolide significantly increased glucose uptake capability. Andrographolide was able to increase the mRNA levels of PPARγ and GLUT‐4 compared to pioglitazone with the best concentration at 5.6 µM. In conclusion, andrographolide can improve glucose uptake by increasing mRNA levels of PPARγ and GLUT‐4 that encodes protein, which are key factors for glucose homeostasis. Therefore, this finding further establishes the potency of andrographolide from A. paniculata as an antidiabetic.